233 DOES OUTPATIENT PRESCRIPTION DRUG BENEFIT LEAD TO BETTER CONTROL OF HIGH BLOOD PRESSURE IN OLDER ADULTS?. (1st January 2005) - Niakan, A.; Shorr, R. I.; Kritchevsky, S. B.; Bush, A.; Cushman, W.; Simonsick, E.; Newman, A. B.; Rooks, R.; Ding, J.; Rubin, S.; Harris, T. B.
Abstract : Background: It is plausible that hypertensive older adults with outpatient prescription drug benefit (OPDB) attain better blood pressure control than those without OPDB; however, this has not been rigorously studied. Methods: We performed a one-year retrospective cohort study among participants in Health ABC, a cohort of 3, 075 well-functioning black and white men and women aged 70-79 years from Memphis, TN, and Pittsburgh, PA. Hypertension (HTN) was defined using JNC-VII criteria. Participants were informed if their blood pressure was elevated. Detailed health and socioeconomic information was obtained at baseline and participants had standardized measurements of blood pressure annually. Results: Of 3075 participants, 1192 (39%) had HTN. Of these, we excluded 20 participants for unknown status of OPDB. After one year, 643/1172 (55%) had persistent hypertension (pHTN), whereas the remaining 541 (45%) had controlled hypertension (cHTN). 402 (55%) of patients with OPDB had pHTN compared to 241 (55%) of those with no OPDB (OR = 1.0, 0.8-1.3). This relationship was unchanged when controlling for other sociodemographic and clinical factors (OR = 0.9, 0.8-1.0). In the multivariable analysis, having previous history of hypertension, hyperlipidemia, and being on antihypertensive medication, increased the odds for pHTN by 21%, 25%, and 28% (p < .03 in all cases) respectively. Depression and hospitalization decreased the odds ratio for pHTN by 47% (p = 012, p = .003 respectively). Conclusion: In this high-functioning older cohort with HTN, less than half achieved good BP control within a year of initial measurement. While OPDB was not associated with achieving control in this population, being on anti-hypertensive medication, hyperlipidemia, and previous history of hypertension were all associated with increased risk of pHTN.